Ambivalence: Employee responses to depersonalized bullying at work. (February 2015) - D'Cruz, Premilla; Noronha, Ernesto
The present article furthers our understanding of the nascent concept of depersonalized bullying by exploring employee responses to the phenomenon. Through a qualitative enquiry of international-facing call centre agents in India, the major theme of 'bounded benefits' captured employees' response of ambivalence. Valuing their professional identity and material returns while ruing the depersonalized bullying of their oppressive work environment, participants recognized that their gains were limited by but inextricably linked to workplace demands. Perceiving no alternative to the continuity of their benefits, participants emphasized positive aspects of their experiences to reduce their misgivings. In contrast to interpersonal bullying where targets are victimized and undergo severe strain such that they usually exit the employer organization, depersonalized bullying entails a dualistic response where well-being and strain coexist and where approach dimensions compensate for avoidance dimensions such that compromise and trade-off facilitate coping.